Shell variability in the stem turtles Proterochersis spp. - Tomasz Szczygielski; Justyna Słowiak; Dawid Dróżdż (PeerJ, 2018)
Background Turtle shells tend to exhibit frequent and substantial variability, both in bone and scute layout. Aside from secondary changes, caused by diseases, parasites, and trauma, this variability appears to be inherent and result from stochastic or externally induced flaws of developmental programs. It is, thus, expected to be present in fossil turtle species at least as prominently, as in modern populations. Descriptions of variability and ontogeny are, however, rare for fossil turtles, mainly due to rarity, incompleteness, damage, and post-mortem deformation of their remains. This paper is an attempt at description and interpretation of external shell variability in representatives of the oldest true turtles, Proterochersis robusta and Proterochersis porebensis (Proterochersidae, the sister group to all other known testudinatans) from the Late Triassic (Norian) of Germany and Poland. Methods All the available shell remains of Proterochersis robusta (13 specimens) and Proterochersis porebensis (275 specimens) were studied morphologically in order to identify any ontogenetic changes, intraspecific variability, sexual dimorphism, and shell abnormalities. To test the inferred sexual dimorphism, shape analyses were performed for two regions (gular and anal) of the plastron. Results Proterochersis spp. exhibits large shell variability, and at least some of the observed changes seem to be correlated with ontogeny (growth of gulars, extragulars, caudals, and marginals, disappearance of middorsal keel on the carapace). Several specimens show abnormal layout of scute sulci, several others unusual morphologies of vertebral scute areas, one has an additional pair of plastral scutes, and one extraordinarily pronounced, likely pathological, growth rings on the carapace. Both species are represented in a wide spectrum of sizes, from hatchlings to old, mature individuals. The largest fragmentary specimens of Proterochersis porebensis allow estimation of its maximal carapace length at approximately 80 cm, while Proterochersis robusta appears to have reached lower maximal sizes. Discussion This is the second contribution describing variability among numerous specimens of Triassic turtles, and the first to show evidence of unambiguous shell abnormalities. Presented data supplement the sparse knowledge of shell scute development in the earliest turtles and suggest that at least some aspects of the developmental programs governing scute development were already similar in the Late Triassic to these of modern forms.